Factors influencing employments preference overseas of Malaysian: A comparative study of university students and working adults - Tan, Lip Hooi; Teoh, Chee Shien (2019)
This study intended to look into the overseas employment preferences towards both university students and working adults in Malaysia. We have examined salary and benefit, job security and career development that will influence on the overseas employment preferences of Malaysian. Structural equation modelling was used to analyze the data from a total of 301 respondents by the university students and working adults in Malaysia. The outcomes of the analyses show that job security has significant relationship with overseas employment preferences of working adults but has no significant relationship with university students. While, career development has significant relationship with the overseas employment references of university students but has no relationship with working adults. However, salary and benefit both have no significant relationship with overseas employment preferences towards university students and working adults.